PENERAPAN SISTEM PENGOLAHAN DATA PENERIMA BANTUAN DANA PROGRAM KELUARGA HARAPAN PADA DINAS SOSIAL KABUPATEN WAY KANAN BERBASIS WEB - Nurmayanti Nurmayanti; Sigit Mintoro (STMIK Dian Cipta Cendikia Kotabumi, 2018)
ABSTRACTPoverty is a condition where there is an inability to fulfill basic needs such as food, clothing, shelter, education and health. Poverty can be caused by a scarcity of means to fulfill basic needs or access to education and health. The problem of poverty is inseparable from a national strategy aimed at realizing social and economic welfare for the people of the country as a whole.The program used in making this data processing system is web-based with the programming language used, namely PHP and MySQL databases which are composed in such a way that makes it easier to build data processing systems to be created. While the system development method used is prototyping with use case system design, activity diagram, and class diagram. The operating system used is Microsoft Windows 7 and Personal Computer (PC) Intel Inside, 2 GB RAM and 500 GB Hard disk.The results of this study are data processing system applications to facilitate PKH HR in completing web-based tasks that can be accessed by PKH Operators and Companions wherever they are.